Mesoporous Palladium N,N’-Bis(3-Allylsalicylidene)o-Phenylenediamine-Methyl Acrylate Resins as Heterogeneous Catalysts for the Heck Coupling Reaction - Mella, Claudio (Materials (Basel), 2019)
Palladium N,N’-bis(3-allylsalicylidene)o-phenylenediamine complex (PdAS) immobilized onto mesoporous polymeric methyl acrylate (MA) based resins (PdAS(x)-MA, x = 1, 2, 5, or 10 wt.%) were successfully prepared as heterogeneous catalysts for the Heck reaction. The catalysts were synthesized via radical suspension polymerization using PdAS as a metal chelate monomer, divinylbenzene and MA as co-monomers. The effect of the PdAS(x) content on the physicochemical properties of the resins is also reported. The catalysts were characterized by using a range of analytical techniques. The large surface area (>580 m(2)·g(−1)) and thermal stability (up to 250 °C) of the PdAS(x)-MA materials allows their application as catalysts in the C–C coupling reaction between iodobenzene and MA in the presence of trimethylamine at 120 °C using DMF as the solvent. The PdAS(10)-MA catalyst exhibited the highest catalytic performance with no significant catalytic loss being observed after five reuses, thereby indicating excellent catalyst stability in the reaction medium.